Pengembangan Budaya Literasi Agama di SMA Negeri 2 Kediri - Maimunatun Habibah (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
The National Literacy Movement (GLN) programmed since 2016 has experienced developments with the emergence of many studies on literacy and literacy programs in schools. Literacy programs are not limited to literacy but also lead to religious literacy. This study seeks to raise the religious literacy program at SMA Negeri 2 Kediri. Based on field research carried out under the light of the Prothero religious literacy concept which was later developed by Gallagher, the study finds that the practice of religious literacy in SMA Negeri 2 Kediri has being carried out through a program of reading the scriptures according to their respective religions guided by the religious literacy reading team. The implementation process takes place through three stages. First, the school principal forms a religious literacy team. Second, the implementation phase which includes the stages of habituation, development, and learning. Third, the assessment stage. The three implementation processes are intended so that the religious literacy program not only leads to the accumulation of knowledge, but slowly increases to the level of daily practice.